The Properties of the Insulation of Grass - Jarawae, Roseleena; Masamoh, Ameenah; Yusoh, Nurfadura (YRU Journal of Science and Technology, 2018)
The main purpose of this paper is to study the properties of the insulation of grass. The ratio of mixture of grass and water timber were investigated with 60:40, 70:30 and 80:20 respectively. The sample were prepared on block size 15x15x3 cm 3 . It was observed the physical and thermal properties. The results found that the density of insulation of grass were 0.020 - 0.021 g/cm 3 .The absorption of the sample were 5.769%, 6.060% and 3.125%. The tensile of all insulation sample around 7.614-8.628 Mpa. The thermal conductivity with ratio of grass and water timber 60:40, 70:30 and 80:20 were 0.0493, 0.0196 and 0.0351, respectively. The results confirm that the insulation of grass with ratio of grass and water timber of 70:30 is the most appropriate to develop the insulation.